Compartmentalization and Transport in Synthetic Vesicles - Schmitt, Christine; Lippert, Anna H.; Bonakdar, Navid; Sandoghdar, Vahid; Voll, Lars M. (Frontiers in Bioengineering and Biotechnology, 2016)
Nano-scale vesicles have become a popular tool in life sciences. Besides liposomes that are generated from phospholipids of natural origin, polymersomes fabricated of synthetic block copolymers enjoy increasing popularity, as they represent more versatile membrane building blocks that can be selected based on their specific physicochemical properties, like permeability, stability or chemical reactivity. In this review, we focus on the application of simple and nested artificial vesicles in synthetic biology. First, we provide an introduction into the utilization of multi-compartmented vesosomes as compartmentalized nano-scale bioreactors. In the bottom-up development of protocells from vesicular nano-reactors, the specific exchange of pathway intermediates across compartment boundaries represents a bottleneck for future studies. To date, most compartmented bioreactors rely on unspecific exchange of substrates and products. This is either based on changes in permeability of the coblock polymer shell by physicochemical triggers or by the incorporation of unspecific porin proteins into the vesicle membrane. Since the incorporation of membrane transport proteins into simple and nested artificial vesicles offers the potential for specific exchange of substances between subcompartments, it opens new vistas in the design of protocells. Therefore we devote the main part of the review to summarize the technical advances in the use of phospholipids and block copolymers for the reconstitution of membrane proteins.